KETERKAITAN EFISIENSI OPERASIONAL DAN PEMBIAYAAN BERMASALAH DALAM MEMPENGARUHI PROFITABILITAS BANK UMUM SYARIAH - Kusumawati, Nugrahini; Setianingsih, Ani (IQTISHODUNA, 2018)
The aimed of this study is to examine the influence of operational efficiency and Non-Performing Financing of The Shariah Bank toward profitability.Â  This study uses secondary data obtained from the annual report contained in Bank Indonesia. The sample in this study used 8 sharia commercial banks registered in Bank Indonesia in 2012-2016. Samples were chosen using purposive sampling methods. The hypothesis was tested using multiple regression. The first hypothesis was used to examine the influence of operational efficiency to profitability. The second hypothesis was used to examine the influence of Non-Performance Financing to profitability. The third hypothesis was used to examine the influence of Operational Efficiency and Non Performance Financing to profitability. The result of the research shows that operational efficiency has an effect on profitability. But operational efficiency has not an effect on profitability. Simultaneously operational efficiency and Non-Performance Financing have an effect on profitability.